Determinants of Frequency and Contents of Postnatal Care Among Women in Ezha District, Southern Ethiopia, 2020: Based on WHO Recommendation - Habte A; Dessu S (Dove Medical Press, 2021)
Aklilu Habte,1 Samuel Dessu2 1Department of Reproductive Health, School of Public Health, College of Medicine and Health Sciences, Wachemo University, Hosanna, Southern Ethiopia; 2Department of Public Health, College of Medicine and Health Sciences, Wolkite University, Wolkite, Southern EthiopiaCorrespondence: Aklilu Habte Hailegebireal Tel +251912744786Email akliluhabte57@gmail.comBackground: Postnatal care is a constellation of preventive care, practices, and assessments intended to detect and treat complications for both the mother and the newborn in the first six following birth. Monitoring of the content and frequency of the PNC is required to make the service provision more successful. However, several studies centered on the general PNC visits, and pieces of evidence were limited at the country level on the core content of the PNC, including the current study area. Therefore, this study aimed to identify determinants of the frequency and content of PNC visits among women who gave birth in the last 12 months in Ezha district, Southern Ethiopia.Methods and Materials: A community-based cross-sectional survey was conducted in the Ezha district to collect data from 568 respondents by using pre-tested, interviewer-administered questionnaires. Data were entered into EpiData3.1 and exported to SPSS version 23 for analysis. To determine the wealth status of the respondents, the Principal Component Analysis was undertaken. To evaluate the determinants of frequency and the content of PNC, both binary logistic regression and generalized linear regression with Poisson type were applied respectively.Results: Nearly a quarter (23.9%) of respondents received three or more postnatal visits, and only 81 (14.6%) respondents received all the PNC service contents suggested by WHO. Identified predictors of the core content of PNC were, frequencies of ANC (AOR: 1.25, 95% CI: 1.15– 1.35), enrollment in community-based health insurance scheme (AOR: 0.69 (95% CI: 0.64– 0.75), and PNC frequency (AOR: 0.64, (95% CI (0.57– 0.73).Conclusion: A low level of WHO-recommended frequency and content of the PNC were identified in the study area. To achieve better utilization, strengthening efforts to improve adequate ANC uptake, enrollment in the CBHI scheme, and working on a model household creation were, therefore, should be crucial measures.Keywords: postnatal care, contents of postnatal care, determinants